Optimized arrays for 2D resistivity surveys with combined surface and buried arrays. Issue 5 (1st July 2015) - Loke, M.H.; Kiflu, H.; Wilkinson, P.B.; Harro, D.; Kruse, S.
ABSTRACT: The 'Compare R' method is used to automatically generate optimized arrays for two‐dimensional resistivity surveys with electrodes arranged along parallel lines on the surface and the subsurface. The resolution at depth is greatly improved by carrying out measurements with at least one line of electrodes below the surface using a direct push installation technique. The performance of the optimized arrays is compared with a standard measurement sequence created manually that was used for previous surveys. Tests were conducted using a synthetic model and a field survey in an area with karst geology that has some ground truth. Both tests show that the optimized arrays have significantly better resolution compared with a standard measurement sequence. We also show that artefacts in the inversion model can be reduced by using higher damping factors near the positions of the subsurface electrodes.